Formula Pelet Berbahan Aktif Trichoderma sp. dan Aplikasinya terhadap Penyakit Rebah Kecambah pada Tanaman Mentimun - Bonny Poernomo Wahyu Soekarno; Surono Surono; Susanti Susanti (Jurnal Fitopatologi Indonesia, 2014)
Cucumber (Cucumis sativus) is an important vegetable comodity in Indonesia, but its production rate is still low. One of the factors that cause the low productivity is plant diseases. Damping-off disease often causes the damage of cucumber plant caused by a fungus that lives in the soil as soilborne disease, Phytium sp. The controlling effort of this disease have been done, for example using Trichoderma sp. as bio-agent, but the utilization of the bio-agent still is not practical so it is difficult to be applied in field. The pellet formula is more effective to be implemented because of the small size and easily moved. The purpose of this research was to produce the pellet formulation with active material of Trichoderma sp.  with rich nutritious content, cheap and easy carrier. This research used two tests, in vitro and in vivo test.  The in vitro test used six different pellet formulations, DAT, UAT, TAT, PAT, DDS and ATS. The best formulation in in vitro test are UAT and DDS, then the formulas were used in in vivo test. Both formulas could suppress the pathogenic fungus, Pythium, in vivo test.